Vitamin C Inhibits Staphylococcus aureus Growth and Enhances the Inhibitory Effect of Quercetin on Growth of Escherichia coli In Vitro - Kallio, Johanna; Jaakkola, Mari; Mäki, Marianne; Kilpeläinen, Pekka; Virtanen, Vesa (Planta Medica, 2012)
Quercetin is a natural flavonoid possessing a number of health beneficial effects. Its bioactivity is restricted by low solubility and sensitivity to oxidative degradation, factors that are often ignored in laboratory studies. We studied the antimicrobial effects of quercetin on Staphylococcus aureus, Escherichia coli and Lactobacillus plantarum at concentrations at which it is soluble and investigated how the antioxidant vitamin C modulates these activities. S. aureus was the most sensitive of the studied bacteria. After 12 hours of culturing, 90 µM quercetin decreased the growth of S. aureus to 75 % of the value for a control culture. 1 mM vitamin C combined with 90 µM quercetin diminished the growth of S. aureus drastically to 3 % of that of the control culture supplemented with vitamin C only. Interestingly, vitamin C by itself inhibited the growth of S. aureus as well, and 5 mM vitamin C inhibited growth completely. The growth inhibition of E. coli was slightly but significantly better in the presence of both quercetin and vitamin C than in the presence of quercetin alone. Probiotic L. plantarum was resistant to quercetin in the presence and absence of vitamin C. Enhancement of quercetinʼs antimicrobial activity by vitamin C is partly explained by the stabilizing effect of vitamin C on quercetin. Even though the acidity of vitamin C contributes to the inhibition of S. aureus growth, neutralized vitamin C also inhibits the growth efficiently even without quercetin. Our results suggest that vitamin C affects the metabolism of S. aureus and that these changes are likely to result in the observed growth inhibition. Although vitamin C itself is a powerful antioxidant, its aerobic metabolism increases oxidative stress on bacterial cells. Vitamin C may therefore be a safe and natural alternative for restricting the growth of S. aureus when non-toxicity is required.
Keywords: vitamin C; quercetin; Staphylococcus aureus; antimicrobial agents; bacterial growth curves